Global attractors for a system of elasticity with small delays - Araujo, Rawlilson O. [UNESP]; Bocanegra-Rodriguez, Lito E.; Calsavara, Bianca M. R.; Seminario-Huertas, Paulo N.; Sotelo-Pejerrey, Alfredo (Wiley-Blackwell, 2021)
This paper is concerned with dynamics of elasticity systems featuring a nonlinear foundation of critical growth and delay effects. The existence of global attractors for such systems has been studied recently. Our main contribution establishes the upper-semicontinuity of attractors with respect to a small parameter multiplying the delay term. Our results are new even for the analogous scalar wave equation.
Keywords: delay; global attractor; Lame system; upper-semicontinuity